2017
DOI: 10.1590/s2175-97902017000115063
|View full text |Cite
|
Sign up to set email alerts
|

Application of HPLC-DAD for the quantification of Lycorine in Galanthus elwesii Hook

Abstract: In the present study, a reversed-phase high-performance liquid chromatographic method has been used for the quantitative determination of lycorine in the aerial parts and bulbs of G. elwesii Hook. A simple method for the extraction of lycorine in low mass plant samples was employed utilizing pre-packed columns with diatomaceous earth (Extrelut®). The chromatographic separation was performed using an isocratic system with a mobile phase of trifluoroacetic acid-water-acetonitrile (0.01:92.5:7.5, v/v/v) applied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…In previous studies, several Galanthus species were reported to contain only lycorine -not galanthamine -as in the results of this study. Finally, lycorine content was calculated to be higher in bulbs than aerial parts in accordance with relevant literature (Kaya et al 2004;Sarıkaya et al 2012;Unver Somer et al 2013;Kaya et al 2014;Emir et al 2017). The fact that the diversity of these alkaloids, their distribution and amounts are different in species and populations, may be explained by infraspecific variations which are influenced by several factors such as polymorphisms in genotype as well as stage of maturity, soil composition and the different climate and drying conditions (Larsen et al 2010).…”
Section: Discussionsupporting
confidence: 70%
“…In previous studies, several Galanthus species were reported to contain only lycorine -not galanthamine -as in the results of this study. Finally, lycorine content was calculated to be higher in bulbs than aerial parts in accordance with relevant literature (Kaya et al 2004;Sarıkaya et al 2012;Unver Somer et al 2013;Kaya et al 2014;Emir et al 2017). The fact that the diversity of these alkaloids, their distribution and amounts are different in species and populations, may be explained by infraspecific variations which are influenced by several factors such as polymorphisms in genotype as well as stage of maturity, soil composition and the different climate and drying conditions (Larsen et al 2010).…”
Section: Discussionsupporting
confidence: 70%
“…For example, galantamine has been reported to be present mostly in the leaves of L. aestivum, the root of G. nivalis and L. vernum, while lycorine has been reported to be present mostly in the root of G. nivalis and L. aestivum, the leaf of L. vernum (Petruczynik et al, 2016), and the bulbs (compared to aerial parts) of G. reginae-olgae subsp vernalis (Conforti et al, 2010). Galantamine and lycorine accumulation in G. elwesii has been reported to be more in the aerial parts in some locations, yet in bulbs in some others (Emir et al, 2017). Similar to previous researches, the results of this research show that galantamine and lycorine accumulation vary depending on the phenological periods and plant parts.…”
Section: Galantamine and Lycorine Contentmentioning
confidence: 99%